Alien flora across European coastal dunes. Issue 3 (19th April 2020) - Giulio, Silvia; Acosta, Alicia Teresa Rosario; Carboni, Marta; Campos, Juan Antonio; Chytrý, Milan; Loidi, Javier; Pergl, Jan; Pyšek, Petr; Isermann, Maike; Janssen, John A. M.; Rodwell, John S.; Schaminée, Joop H. J.; et al.
Abstract: Questions: The spread of alien plant species is one of the main threats to the biodiversity of different natural habitats, and coastal dune habitats are among the most affected. There is a considerable local and regional variation in the level of alien plant invasion on coastal dunes. We asked what are the patterns of invasion across European coastal dunes and how they depend on habitat types and coastal regions. Location: Atlantic, Baltic, Black Sea and Mediterranean coasts of Europe. Methods: We used vegetation‐plot records from shifting dunes and stable dune grasslands extracted from the European Vegetation Archive (EVA). We quantified richness, frequency and distribution of alien plant (neophyte) species across dune habitats and coastal regions. We also explored the donor habitats and invasion trajectories of these species. Results: In the flora of European coastal dunes, 7% of species were neophytes, for two‐thirds originating from outside of Europe and mostly naturalised and ruderal. Shifting and stable dunes were similar in neophyte species composition, but there were more individual occurrences of neophytes in shifting dunes. The neophyte flora composition differed considerably between the Atlantic, Baltic, Black Sea and Mediterranean regions. The highest number of neophyte species was observed on the Atlantic dunes, while the highest number of neophyte occurrences was on the Black Sea dunes. Most of the neophytes originated from North America and the Mediterranean‐Turanian region. Erigeron canadensis, Xanthium orientale, Oenothera biennis and Oenothera oakesiana were the most common neophytes. Conclusions: We provided a comprehensive assessment of alien plant invasions in the coastal dunes across Europe and highlighted that coastal dunes should be in the focus of European invasion management strategies. Abstract : Using vegetation‐plot records from the EVA, we quantified the level of invasion on European shifting and stable dunes, highlighting differences in invasion patterns across regions. Neophytes comprised 7% of the total dune flora, and two‐thirds of these originated outside of Europe. Atlantic dunes were the main recipients of neophytes, while the Mediterranean Basin was also an important donor.